Exploring the Value of AI Technology in Optimizing and Implementing Supply Chain Data for Pharmaceutical Companies - Wu Guo (Innovation in Science and Technology, 2023)
The adoption of artificial intelligence (AI) in the pharmaceutical industry has the potential to revolutionize supply chain management, enabling pharmaceutical companies to optimize their logistics and production processes while improving product quality and overall patient safety. This paper explores the value of AI technology in optimizing and implementing supply chain data for pharmaceutical companies. It reviews case studies from leading pharmaceutical companies such as Pfizer, Amgen, GlaxoSmithKline, Merck, and Roche, and examines how they are leveraging AI-powered solutions to optimize their logistics, production, and quality control processes. The paper finds that AI-powered solutions provide several benefits, including enhancing the accuracy, speed, and efficiency of supply chain management, reducing costs, and ensuring compliance with regulatory requirements. The authors advocate for increased investment in AI technology to fully realize the potential of these solutions in the pharmaceutical industry. The paper concludes that the adoption of AI in pharmaceutical supply chain management is critical for improving patient outcomes and ultimately driving the success of pharmaceutical companies in a rapidly evolving healthcare landscape.